1984
DOI: 10.1161/01.cir.70.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of timolol for prevention of supraventricular tachyarrhythmias after coronary artery bypass surgery.

Abstract: Forty-one patients undergoing coronary artery bypass grafting were randomly assigned to receive prophylactic timolol or placebo, given in a double-blind fashion. /3-Adrenoceptor-blocking therapy was stopped at least one half-life before surgery. Three to 7 hr after surgery (304 + 56 min), 0.5 mg of timolol or placebo was given intravenously twice daily in a double-blind manner. When oral medications were resumed postoperatively, 10 mg of timolol twice daily or placebo was continued orally. Continuous electroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(47 citation statements)
references
References 12 publications
3
40
1
3
Order By: Relevance
“…The efficacy and safety of intravenous propranolol 18 and intravenous timolol 19 have been studied earlier in the prevention of AF after cardiac surgery. These studies concluded that both ␤-blockers were effective in AF prophylaxis when compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of intravenous propranolol 18 and intravenous timolol 19 have been studied earlier in the prevention of AF after cardiac surgery. These studies concluded that both ␤-blockers were effective in AF prophylaxis when compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AF after elective CABG surgery has been reported in a very wide range, from 5-70% 6,16,17 . A large, prospective, observational, international, multicentre study of 4657 patients published in 2004 found the occurrence of POAF in 32.2% of patients undergoing isolated CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…That is why the ESC guidelines for the management of atrial fibrillation recommend that treatment should be started at least 1 week before surgery with a beta 1 -blocker without intrinsic sympathomimetic activity (Camm et al, 2010). The beta-blockers used in studies assessing atrial fibrillation prevention in cardiac surgery were propranolol (Matangyi et al, 1985), atenolol (Lamb et al, 1988), metoprolol (Lucio et al, 2004Kamei et al, 2006;Celik et al, 2009), acebutolol (Daudon et al, 1986), timolol (White et al, 1984), carvedilol (Kamei et al, 2006;Celik et al, 2009), betaxolol (Iliuta et al, 2009), either compared to control or to another beta-blocker.…”
Section: Discussionmentioning
confidence: 99%